Dysregulated Urinary Arginine Metabolism in Older Adults With Amnestic Mild Cognitive Impairment - Zhang, Yue-qi; Tang, Ya-bin; Dammer, Eric; Liu, Jian-ren; Zhao, Yu-wu; Zhu, Liang; Ren, Ru-jing; Chen, Hong-zhuan; Wang, Gang; Cheng, Qi (Frontiers in Aging Neuroscience, 2019)
Background: Urine samples are ideal for exploration of non-invasive biomarkers to confirm amnestic mild cognitive impairment (aMCI) status of patients versus unimpaired ones. Objective: We aimed to detect differentially metabolized amino acids from urine of aMCI patients, which may give clinicians the possibility to intervene with early treatments that curb Alzheimer’s Disease (AD). Methods: The study included 208 subjects, 98 of them were aMCI patients, and 110 were control subjects without dementia. Urine samples were taken from each participant and supernatant was obtained for analysis. The concentrations of amino acids were measured by liquid chromatography-tandem mass spectrometry (LC-MS/MS). Results: Urine arginine levels and its metabolites, ornithine in aMCI patients are obviously lower than in normal controls (q<0.2 and p＜0.05). Meanwhile, aMCI patients had significant reduced urine global arginine bioavailability ratio (GABR), and GABR in urine displayed a positive correlation with the score of MMSE. Conclusion: Urine dysregulated arginine metabolism that may serve as a helpful clinical diagnostic biomarker for aMCI in older adults.